Phase III clinical trial (RERISE study) results of efficacy and safety of radotinib compared with imatinib in newly diagnosed chronic phase chronic myeloid leukemia - Jae Yong Kwak (2018)
©2017 AACR. Purpose: Radotinib is a second-generation BCR-ABL1 tyrosine kinase inhibitor (TKI) approved in Korea for chronic phase chronic myeloid leukemia (CML-CP) in patients newly diagnosed or with insufficient response to other TKIs. This study was conducted to evaluate the efficacy and safety of radotinib as first-line therapy for CML-CP. Experimental Design: This multinational, open-label study assigned patients (1:1:1) to one of two twice-daily radotinib doses, or imatinib daily. The primary endpoint was major molecular response (MMR) by 12 months. Results: Two hundred forty-one patients were randomized to receive radotinib 300 mg (n ¼ 79) or 400 mg twice-daily (n ¼ 81), or imatinib 400 mg daily (n ¼ 81). MMR rates by 12 months were higher in patients receiving radotinib 300 mg (52%) or radotinib 400 mg twice-daily (46%) versus imatinib (30%; P ¼ 0.0044 and P ¼ 0.0342, respectively). Complete cytogenetic response (CCyR) rates by 12 months were higher for radotinib 300 mg (91%) versus imatinib (77%; P ¼ 0.0120). Early molecular response at 3 months occurred in 86% and 87% of patients receiving radotinib 300 mg and radotinib 400 mg, respectively, and 71% of those receiving imatinib. By 12 months, no patients had progression to accelerated phase or blast crisis. Most adverse events were manageable with dose reduction. Conclusions: Radotinib demonstrated superiority over imatinib in CCyR and MMR in patients newly diagnosed with Philadelphia chromosome–positive CML-CP. This trial was registered at www.clinicaltrials.gov as NCT01511289.